Topic: Distribution of Anopheles stephensi bioforms in selected districts of Rajasthan, India - Sangeeta Singh; Robin Marwal; Suman Lata; Poonam Saroha; Sanjeev Kumar Gupta; Himmat Singh (PLoS ONE, 2025)
Introduction Anopheles stephensi is a major urban malaria vector in Rajasthan, India, and is responsible for spreading persistent malaria throughout the year. In Rajasthan, An. stephensi is invariably distributed and has three bioforms discriminated based on the number of the ridge on the eggs viz; Type, Mysorensis, and Intermediate. The present study aimed to understand the distribution pattern of these bioforms in rural and urban setups as they also have differences in their malaria transmission capacity. Methods Gravid mosquitoes and the larvae were collected from different habitats of districts of Rajasthan. The gravid females An. stephensi were allowed to lay eggs. These eggs then were subjected to morphometric analysis and counted for the number of ridges for bioform identification. Results About 15000 ± 200 eggs were obtained from ~190 gravid An. stephensi collected from 45 localities (11 Urban & 34 Rural) of eight districts of Rajasthan. Out of which 3569 eggs were subjected to morphometric analysis. Mysorensis bioform (49.7%) was observed to have higher percent over Intermediate (25.5%) and Type (24.6%) bioforms. Mysorensis and Intermediate were found more in rural areas whereas the Type bioform dominated higher in urban areas. Discussion The Mysorensis bioform was found to be dominant throughout the year in all seasons in rural areas. Type bioform preferred indoor breeding places like underground tanks, cement tanks whereas other bioforms preferred outdoor breeding places. Egg size was found to be directly proportional to the number of ridges on the eggs (r = 0.55). No reproductive isolation was observed among these bioforms. Conclusions The Mysorensis bioform is more prominent than other bioforms. Subspecies level understanding helps to plan effective control measures according to the breeding site selection majorly by Type bioform, an efficient vector in this region.